How airline service post COVID-19 pandemic? Domestic LCC passenger perception in Indonesia - Irfan Rifai Andri; Manao Agusman; Handayani Susanty (E3S Web of Conferences, 2023)
Domestic Low-Cost Carrier (LCC) airlines are the primary choice for travelers when traveling during the post-pandemic COVID-19. Indonesia is a country with quite a lot of flight routes with various LCC services. This research was conducted on domestic LCC services in Indonesia during the Post COVID-19 pandemic, completed in December 2022 and January 2023. Data were obtained using a questionnaire with 100 respondents using a Linkert scale. Analysis of the data was carried out using Importance Performance Analysis and Customer Satisfaction Index. The research results show exciting things. Based on the results of the CSI calculation, it is 74.72%. This result means that domestic LCC passengers consider the airline's service Fair. The results of mapping the level of importance and performance of domestic LCC obtained two attributes included in the main priority: Information to passengers in the event of a delay and maintenance and availability of cleaning facilities on the plane. In addition, the Convenience dimension is a priority that must be considered by domestic LCC airlines in Indonesia.